Identification of Immune-Related Breast Cancer Chemotherapy Resistance Genes via Bioinformatics Approaches - Du, Yabing; Han, Yikai; Wang, Xin; Wang, Huanrong; Qu, Yanhong; Guo, Kaiyuan; Ma, Wang; Fu, Lijun (Frontiers in Oncology, 2022)
Chemotherapy resistance in breast cancer is an important factor affecting the prognosis of breast cancer patients. We computationally analyzed the differences in gene expression before and after chemotherapy in breast cancer patients, drug-sensitive groups, and drug-resistant groups. Through functional enrichment analysis, immune microenvironment analysis, and other computational analysis methods, we identified PRC1, GGTLC1, and IRS1 as genes that may mediate breast cancer chemoresistance through the immune pathway. After validation of certain other clinical datasets and in vitro cellular assays, we found that the above three genes influenced drug resistance in breast cancer patients and were closely related to the tumor immune microenvironment. Our finding that chemoresistance in breast cancer could be influenced by the mediation of tumor immunity expanded our knowledge of how to address this problem and could guide future research involving chemoresistance.